Effective management of maritime security in shipping companies - Sadovaya, Elena (2015)
During the last ten years, maritime security has become an important issue on the international maritime agenda. The diversity of security requirements brings a problem of effective security management in shipping companies and may impact their organizational performances significantly. Therefore, this research project aims to develop and validate an Effective Maritime Security Management Model (EMSMM) for shipping companies and to study its impacts on their organizational performance. It addresses three main research questions, focusing on maritime security regulations and requirements, effective maritime security management, and its impacts on organizational performance. A comprehensive literature review was conducted to study existing maritime security regulations and management approaches as well as earlier proposed models and systems applicable for security management to derive a detailed list of compulsory and voluntary security requirements imposed on shipping companies and essential criteria for the EMSMM. Besides, the literature on reported and proposed impacts of security management on organizational performance of shipping companies was analyzed and the list of impacts was composed. Based on the reviewed literature, the EMSMM was developed. To empirically validate the model, thirteen in-depth interviews, one main survey and one confirmatory survey were conducted. The sampling population was constructed from industry practitioners responsible for security management in shipping companies worldwide. To analyse the collected information, thematic and statistical methods as well as the analytical hierarchy process (AHP) technique were applied in this study. Statistical methods, such as the exploratory and confirmatory factor analyses (EFA and CFA) and the structural equation modelling (SEM), were used to validate the EMSMM and to analyse its impacts on the organizational performance of the participating companies. Further, to rank the importance of the model’s factors, the AHP technique was applied. The results confirmed that the EMSMM consists of six factor, namely, Management and Employee Commitment, Security Policy, System and Procedures, Security Assessment, Security Incidents Handling and Continuity of Operations, Business Partners Security, and Documentation and Communication. The impacts of security management on organizational performance were measured according to three categories of performance, namely, Security Performance, Business Resilience and Other Organizational Performance, where the last category was further divided into Security Related, Time, Customer and Market Performance. The results of this project confirmed the overall positive impact of the proposed EMSMM on the organizational performance of shipping companies. However, it is important for managers to implement all factors together in order to achieve these positive results. Apart from enriching the literature on maritime security management, the proposed model can be used as a security management toolbox which can help senior management in shipping companies to manage security effectively. However, further research is needed to study the relationship between the EMSMM and Business Resilience, since this relationship is not significant due to the shortage of data on actual security accidents.